Topical Biocomposites Based on Collagen, Hyaluronic Acid and Metronidazole as Periodontitis Treatment - Madalina Georgiana Albu Kaya; Alice Geanina Simonca; Ileana Rau; Alina Elena Coman; Minodora Maria Marin; Lacramioara Popa; Roxana Trusca; Cristina-Elen; Mihaela Violeta Ghica (MDPI AG, 2024)
Background: It is well known that periodontitis affects the gums and surrounding connective tissue. The chronic inflammatory response induced by bacteria in the gingival tissue leads to the loss of the collagen connection between the tooth and the bone and ultimately to bone loss. Methods: In this context, the aim of this research was the obtaining and characterization of a drug release supports in the form of sponges based on collagen, hyaluronic acid as a support and metronidazole as an antibiotic for the treatment of periodontitis. The sponges were characterized by FT-IR spectroscopy, water uptake, contact angle, SEM microscopy, in vitro metronidazole release analysis from sponges and data modeling. Results: The results showed that all the sponges had a porous structure with interconnected pores, the pore sizes being influenced by hyaluronic acid and metronidazole; the spongious structure became much more dense for samples with metronidazole content. All metronidazole-loaded sponges showed good surface wettability and an adequate swelling capacity for a suitable antimicrobial release at the periodontal pocket. The porous structures allow a controlled release, fast in the first hour, essential to control the initial microbial load at the periodontal level, which continues slowly in the following hours to ensure an effective treatment of periodontitis. Conclusions: Correlating all physical-chemical and bio-pharmaceutical results obtained, a promising solution for periodontitis treatment could be a met-ronidazole-collagen-hyaluronic system consisting of 1% collagen, 1.5% metronidazole and 0.8% hyaluronic acid, and in vitro and in vivo tests are recommended to continue studies.